Manajemen Strategi Pengawas Madrasah dan Pengawas Pendidikan Agama Islam dalam Upaya Meningkatkan Mutu Pendidikan Islam di Provinsi Kepulauan Riau (Pendekatan Kebijakan, Implementasi, dan Evaluasi PMA Nomor 31 Tahun 2013) - Saleh, Khairul (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper outlines that academic and managerial supervision of education is a crucial component in improving the quality of Islamic education in both madrasahs and public schools. This article reviews the strategic management applied by Madrasah Supervisors and Islamic Religious Education Supervisors in Riau Islands Province to enhance the quality of Islamic education. The focus is on the policy approach, implementation, and evaluation of Minister of Religious Affairs Regulation (PMA) Number 31 of 2013 concerning Islamic education supervisors. The method used in this discussion is descriptive qualitative, with data collection through policy document analysis and interviews with relevant stakeholders. The goal is to identify how supervision strategies are formulated, implemented, and evaluated to achieve higher educational quality standards. The analysis results indicate that while PMA Number 31 of 2013 has become an important foundation, its implementation faces several challenges. The implementation of academic supervision in madrasahs and public schools has not been carried out well according to existing regulations. This finding suggests that the academic supervision function, which aims to improve the quality of learning, has not been optimally implemented. An analysis using a strategic management theoretical framework reveals that a primary cause is the lack of training to enhance supervisors' competence in academic supervision. As a result, there are recommendations for increasing the capacity and competence of Madrasah Supervisors and Islamic Religious Education (PAI) Supervisors. All of these efforts aim to optimize the role of supervisors in improving the quality of Islamic education in Riau Islands Province.